Protective effect of platelet-rich fibrin (PRF) against dry socket following surgical extraction of the mandibular third molar - Nosheen Iqbal; Muhammad Usman Khalid; Omer Sefvan Janjua (Journal of University Medical & Dental College, 2025)
BACKGROUND & OBJECTIVE: Dry socket (DS) is one of the most painful complications following tooth extraction. Various preventive measures have been suggested over the years, but results remain inconclusive. This study aimed to evaluate the protective effect of Platelet-Rich Fibrin (PRF) against DS after surgical removal of impacted mandibular third molars. METHODOLOGY: A total of 170 consecutive patients fulfilling the inclusion criteria (age 18–35 years, good oral hygiene, and requiring surgical extraction of mandibular third molars) were enrolled and randomly assigned into two equal groups (85 each). A standardized surgical protocol was followed in all cases. Group 1 (study group) received PRF placement in the socket, while Group 2 (control group) did not. RESULTS: The mean age was 24.28 ± 3.7 years in the study group and 24.14 ± 3.64 years in the control group. Overall, 87 participants (51.2%) were male and 83 (48.8%) female. On the 3rd postoperative day, the incidence of DS in the PRF group was 2 cases (2.4%), compared to 16 cases (18.8%) in the control group, showing a statistically significant difference (p = 0.0004). No significant association was observed between DS occurrence and factors such as side of extraction, type of impaction, angulation, or bone removal. CONCLUSION: Placement of PRF in extraction sockets significantly reduces the risk of DS following mandibular third molar surgery. Its routine application is recommended to improve postoperative outcomes and reduce patient morbidity.